EFEKTIVITAS PENGAWASAN TAHAPAN KAMPANYE OLEH PANWASLU KECAMATAN CIAMIS PADA PEMILIHAN UMUM TAHUN 2024 - Pramulya, Diwan; Supena, Cecep Cahya (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The campaign stage is a crucial and significant phase in the General Elections in Indonesia, as stipulated in Law Number 7 of 2017 concerning Elections and further regulated in the General Elections Commission Regulation Number 15 of 2023 concerning Election Campaigns, as well as the Election Supervisory Body Regulation Number 11 of 2023 concerning Campaign Supervision. However, during the implementation of the campaign stage in the 2024 General Elections, alleged campaign violations that disrupt the integrity of the elections were still frequently found. This study aims to analyze the effectiveness of campaign stage supervision by the Ciamis District Panwaslu (Election Supervisory Committee) in the 2024 General Elections by examining the implementation of supervisory duties and authorities in accordance with applicable regulations. The research method uses a descriptive qualitative approach, with data collection techniques through in-depth interviews, documentation, and observation of campaign supervision activities carried out by the District Panwaslu. The results of the study indicate that the Ciamis District Panwaslu has carried out its campaign monitoring functions in accordance with the provisions of the legislation. Supervision was conducted through monitoring patrols, the reception and handling of reports, and coordination with stakeholders. Nonetheless, its effectiveness is still hindered by limitations in human and logistical resources, as well as a low level of public participation. This study recommends enhancing the institutional capacity of Panwaslu and strengthening regulation-based participatory supervision.